Low glomerular number at birth can lead to the development of chronic kidney disease - Fukunaga, Shohei; Fujita, Yuki (Frontiers in Endocrinology, 2023)
Chronic kidney disease (CKD) prevalence is increasing worldwide, and reducing the number of patients with CKD is of utmost importance. The environment during the fetal, perinatal, and early childhood stages may influence CKD development (developmental origins of health and disease). Under conditions of maternal malnutrition, the glomerular number of infants is reduced, and the risk of developing CKD may increase. Nephron progenitor cells and ureteric buds interact with each other to form glomeruli at the tip of the ureteric bud. Thus, the number of glomeruli is determined by the number of ureteric bud branches, which are reportedly decreased due to maternal malnutrition, in turn reducing the glomerular number. Four possible mechanisms can explain the low glomerular number resulting from maternal malnutrition: 1) suppression of c-Ret expression, 2) suppression of nephron formation by renin-angiotensin-aldosterone system inhibition, 3) exposure to excess glucocorticoids, and 4) promotion of apoptosis. Additionally, nephron formation does not continue after birth in humans. Therefore, a low glomerular number at birth is a lifelong burden on the glomeruli and increases the risk of developing CKD. Therefore, it is important to maintain the glomerular number at birth. Accurate glomerular counts are essential for conducting studies on the glomerular number. The dissector/fractionator method is the gold standard; however, it can only be performed at some institutions. Recently, methods have been developed to measure the glomerular number by combining computed tomography and pathological examination and measure the glomerular count using magnetic resonance imaging. Models of decreased and increased glomerular numbers have been developed. Moreover, research regarding the causes of decreased glomerular number and its relationship with development of lifestyle-related diseases and renal dysfunction has significantly progressed, furthering our understanding of the importance of the glomerular number.